Innovation portfolio management for the public non-profit research and development sector: What can we learn from the private sector? - Schut, Marc; Addom, Benjamin K.; Proud, E.; Dror, Iddo; Barrett, Christopher B.; Menzies, D.; Colomer, Julien; Leeuwis, C. (Informa UK Limited, 2024)
Innovation Portfolio Management refers to the systems, processes andmechanisms to intentionally manage innovation investments anddecisions within an organization against its mission or strategy. Thisapproach to managing and optimizing innovation and scalinginvestments is rarely used by public non-profit R&D organizations.This study draws lessons from innovation portfolio management inprivate sector organizations. Private sector invests in innovationportfolio management to: (i) enhance transparent and evidence-based decision-making, (ii) strengthen organizational agility andmission-orientedness, (iii) facilitate monitoring, risk management andprioritization and (iv) improve overall organizational performanceand learning. These innovation portfolio management benefits areequally relevant for the public non-profit R&D sector, whereinnovation performance and outcomes are for societal impact. Publicnon-profit R&D can and should manage their innovation portfoliosmore intentionally, and can learn from private sector successes andchallenges. Embracing the opportunities, whilst managing thechallenges and risks requires investment in methods, mechanismsand mindsets for effective innovation portfolio management.